2016
DOI: 10.1542/hpeds.2015-0095
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Refusal of Newborn Vitamin K Prophylaxis: Implications for Management and Education

Abstract: This study provides an understanding of the concerns, mindset, and information sources used by parents refusing IM vitamin K. Educating parents about the importance of IM prophylaxis should begin in the prenatal period and must address concerns parents identify on the Internet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 37 publications
4
48
0
Order By: Relevance
“…In our study, almost one-third of infants born in birthing centers did not receive the vitamin K injection. This finding is also similar to that of a recent study in North Carolina, which found a higher rate of vitamin K refusal at birthing centers than hospitals (Hamrick et al 2016). Variation in frequency of vitamin K refusal by delivery site may be due to inherent differences in the philosophies of parents who choose alternatives to delivering in hospitals, or may reflect the attitudes of providers at such facilities and the education they provide to parents.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In our study, almost one-third of infants born in birthing centers did not receive the vitamin K injection. This finding is also similar to that of a recent study in North Carolina, which found a higher rate of vitamin K refusal at birthing centers than hospitals (Hamrick et al 2016). Variation in frequency of vitamin K refusal by delivery site may be due to inherent differences in the philosophies of parents who choose alternatives to delivering in hospitals, or may reflect the attitudes of providers at such facilities and the education they provide to parents.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, 31% of infants born at birthing centers in Tennessee did not receive vitamin K, compared with 10.7% of infants born at birthing centers in Alberta (Sahni et al 2014), and 4.34 and 8.33% at two birthing centers in North Carolina (Hamrick et al 2016). As in the other studies, rates of refusal for hospital births are low; however, in the Nashville area, rates of refusal are near 3%, which is nearly 10 times higher than the 0.2% refusal rate in Alberta (Sahni et al 2014).…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…One recent study used a survey to ask parents about their concerns regarding vitamin K and where they got their information from. The most common source of information for parents was the internet and the most common concerns were centred on synthetic or perceived toxic ingredients in the formula, excessive dose and side effects 14. However, no other studies have undertaken in-depth interviews with parents.…”
Section: Introductionmentioning
confidence: 99%